Improved Bloch‐Siegert based B1 mapping by reducing off‐resonance shift. (28th January 2013) - Duan, Qi; van, Peter; Duyn, Jeff
<x xml:space="preserve">Abstract</x> An MRI method based on the Bloch‐Siegert (BS) shift phenomenon was recently proposed as a fast and precise way to map a radio frequency (RF) transmit field (B1+ field). For MRI at high field, the mapping sensitivity of this approach was limited by tissue heating associated with a BS irradiation pulse. To mitigate this, we investigated the possibility of lowering the off‐resonance frequency of this pulse since theoretical analysis indicated that the sensitivity of Bloch‐Siegert based B1+ mapping could be substantially improved when irradiating closer to resonance. Using optimized irradiation pulse shape and gradient crushers to minimize direct excitation effects, in vivo experiments on human brains at 7 T confirmed improved sensitivity with this approach. Improved sensitivity translated into an 80% reduction in B1+ estimation errors without increasing tissue heating. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.